KONSEP DIRI DALAM EKSISTENSIALISME ROLLO MAY - Hermawan, Ucep - (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2021)
This reaserch focuses on self as a fundamental requirement for the philosophy of existentialism, the first step in trying to understand the self-concept according to Rollo May. Then look for teh root of the philosophical problem that makes man lose himself until finaly unable to exist in the world. Rollo May is one of the psychologist who brought the philosophical tradition of existensialism to America. In this reaserch, the wraiter places Rollo May as an existentialist philosopher, with depart from the problem of self-philosopy.